Feeding habits of the spider crab Libinia spinosa H. Milne Edwards, 1834 (Decapoda, Brachyura) in Ubatuba Bay, São Paulo, Brazil - De Paiva Barros, Samara; Cobo, Valter José; Fransozo, Adilson [UNESP] (FapUNIFESP (SciELO), 2008)
The main goal of this study was the identification of the items of the diet of the L. spinosa, based on the stomach contents analysis. The crabs were obtained from Ubatuba region north-eastern shore of São Paulo State. In the laboratory, all the individuals were dissected, the stomach was retreated and fixed in 10% formaline. The alimentary items were identified under stereomicroscope and analysed by the method of Frequency of Occurrence. A total of 194 stomachs was analysed and nine alimentary items were obtained. Unindentified material was found in 98% of analysed stomach and poriferan were present in less then 1% of stomachs. These results pointed a diversified diet explored by this crab, as well as the employment of some different methods for food intake. This suggested that these crabs could occupy different position in the trophic chain.
Keywords: Alimentary itens; Spider crab; Stomach contents